Repair Project Acceleration Strategy of Three Ship Units using Fuzzy Logic Analysis and Critical Path Method - Hidayatus Ubyani; Tuswan Tuswan; Hartono Yudo; Haris Nubli; Ocid Mursid; Muhammad Iqbal (Universitas Sebelas Maret, 2023)
This research uses the Critical Path Method (CPM) to analyze the main schedule of three combined ship repair projects. Then, shop-level planning is used to determine the productivity of each workshop so that each workshop knows the volume of work that needs to be completed daily. Furthermore, fuzzy logic is applied to analyze the risk of delays in repair project activities. The addition of working hours to critical work activities is accelerated from 30 days, the normal duration, to 23 days. Meanwhile, the addition of the workforce to critical work activities is accelerated from 30 days, the normal duration, to 22 days. The analysis of productivity values in each workshop results in the following productivity values: sandblasting and painting workshop 309.97 m2/person-days, piping workshop 4.12 units/person-days, fabrication workshop 407.16 kg/person-days, outfitting workshop 14.8 units/person-days, tank cleaning workshop 114.36 m3/person-days, and machining workshop 2.7 units/person-days. The fuzzy logic analysis results to determine the risk of delays in critical activities show that jobs with the codes SP1, SP2, SP3, SP4, M2, and SP5 have high risk of delay. Additionally, the collaboration with other departments in the company, such as the marketing, finance, and human resources departments, is ongoing to complete assigned tasks.